Characterization of thermophysical properties of sorghum (Sorghum bicolor (L.) Moench) using Differential Scanning Calorimetry (DSC) - Anusuya, E; Pandiarajan, T; Balakrishnan, M; Gurusamy, K; Nidoni, U; Eswari, A (Plant Science Today, 2025)
Sorghum (S. bicolor (L.) Moench) is a significant cereal crop globally, renowned for its nutritional value, drought resistance and versatile applications in food, feed and industrial products. In this study, thermal properties of sorghum were investigated using DSC and Line Heat Source method. Thermal analysis via DSC revealed distinct phase transitions, with the glass transition temperature observed at 70 °C and gelatinization phenomena occurring within the temperature range of 69.5 - 83.3 °C, exhibiting a characteristic endothermic peak at 77 °C. The specific heat capacity was quantified in the range 1.3298 - 1.4522 kJ/kg°C with increasing moisture content and enthalpy was computed as 10.2 kJ/kg. Examination of thermal conductivity as a function of moisture content demonstrated a systematic increase in conductivity values, yielding measurements of 0.094, 0.132, 0.156, 0.189, 0.221, 0.252 W/m°C corresponding to moisture contents of 10, 12, 14,16,18 and 20 % (wet basis) (w.b.) respectively. While thermal diffusivity values ranged from 1.52 x 10-4 to 9.61 x 10-5 m2/s. The implementation of DSC methodology facilitated precise characterization of phase transitions and thermal behaviour, generating critical data for various thermal processing operations. These findings constitute significant contributions to the theoretical framework necessary for enhancing process optimization and product quality in sorghum-based applications.